Direct Acting Antiviral Drugs: Pharmacokinetics and Drug-Drug Interactions - Marina Barakat; Sara Wahdan; Azza Awad; Ebtehal El-Demerdash Zaki (Ain Shams University, 2022)
Hepatitis C (HCV) is a widespread health issue, which can lead to hepatic cirrhosis, liver failure, and liver cancer. Nearly 2% of the world's population or > 185 million people are chronically infected with HCV; the management of HCV and the rate of sustained virological response (SVR) were significantly assisted by direct-acting antiviral medications. Since 2014, the FDA has approved using the most potent direct-acting antiviral drug (DAA) combinations. The majority of DAAs can affect cytochrome P450 (CYP) enzymes and are extensively processed by liver enzymes. Additionally, these DAAs are both substrates and drug transporters' inhibitors, making them a potential target for drug-drug interactions (DDIs). As a result, understanding and managing DDIs with DAAs must be regarded as a crucial aspect of the treatment of HCV. Additionally, patients taking numerous medications or having various co-morbidities must be made aware of the potential consequences of DDIs, such as elevated toxicity or an absence of pharmacological efficacy, in current HCV treatments.